2011
DOI: 10.1051/0004-6361/201016196
|View full text |Cite
|
Sign up to set email alerts
|

Galaxy morphology, luminosity, and environment in the SDSS DR7

Abstract: Aims. We study the influence of the environment on the evolution of galaxies by investigating the luminosity function (LF) of galaxies of different morphological types and colours at different environmental density levels. Methods. We construct the LFs separately for galaxies of different morphology (spiral and elliptical) and of different colours (red and blue) using data from the Sloan Digital Sky Survey (SDSS), correcting the luminosities for the intrinsic absorption. We use the global luminosity density fi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 102 publications
(146 citation statements)
references
References 83 publications
6
138
0
1
Order By: Relevance
“…For each galaxy, we have estimated the galaxy morphology as described in Tempel et al (2011). In Tempel et al (2012) the morphologies were compared with those provided by Huertas-Company et al (2011), and a very good agreement was found.…”
Section: Group and Galaxy Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For each galaxy, we have estimated the galaxy morphology as described in Tempel et al (2011). In Tempel et al (2012) the morphologies were compared with those provided by Huertas-Company et al (2011), and a very good agreement was found.…”
Section: Group and Galaxy Propertiesmentioning
confidence: 99%
“…Figure 6 shows the luminosity function in the r-filter for our final sample of the SDSS galaxies. It was calculated using an adaptive smoothing kernel as described in Tempel et al (2011). The vertical lines mark the limits for the different volumelimited samples described above.…”
Section: Group and Galaxy Propertiesmentioning
confidence: 99%
“…This makes them ideal laboratories to study processes that affect the evolution of galaxies, groups, and clusters of galaxies. A number of studies have already shown that the supercluster environment affects the properties of galaxies, groups, and clusters located there (Einasto et al 2003b;Plionis 2004;Wolf et al 2005;Haines et al 2006;Einasto et al 2007c;Porter et al 2008;Tempel et al 2009;Fleenor & Johnston-Hollitt 2010;Tempel et al 2011;Einasto et al 2011). Other evidence about the influence of the largescale environment of galaxies on their properties comes from the study of the properties of galaxies in void walls (Ceccarelli et al 2008) and from the study of the large-scale environment of quasars (Lietzen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The calculation of luminosities is described in Appendix A (details of this calculation are given also in Tempel et al 2011).…”
Section: Datamentioning
confidence: 99%
“…For example, rich superclusters contain high-density cores that may contain merging X-ray clusters and may be collapsing (Small et al 1998;Bardelli et al 2000;Einasto et al 2001;Rose et al 2002;Einasto et al 2007cEinasto et al , 2008. A supercluster environment with a wide range of densities affects the properties of galaxies, groups, and clusters located there (Einasto et al 2003b;Plionis 2004;Wolf et al 2005;Haines et al 2006;Einasto et al 2007d;Porter et al 2008;Tempel et al 2009;Fleenor & Johnston-Hollitt 2010;Tempel et al 2011;Einasto et al 2011b). Einasto et al (2011b) showed that the dynamical evolution of one of the richest superclusters in the Sloan Great Wall (SCL 111, SCl 024 in L10 catalogue) is almost finished, while the richest member of the Wall, SCl 126 (SCl 061) is still dynamically active.…”
Section: Discussionmentioning
confidence: 99%